Resources: Social protection - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
IFPRI’s mission is to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. Recent publications and websites provide critical knowledge and analysis on social protection programs and their contribution to food security, nutrition, and well-being.